A conversation with Douglas W. Jones and Peter G. Neumann. - O'Hanlon, Charlene (New York ACM, 2006)
Does technology help or hinder election integrity?
Keywords: Computing Milieux; Legal aspects of computing; Governmental issues; Computers and Society; Public Policy Issues; Abuse and crime involving computers; Social issues